Analysis of students with psychiatric disabilities in higher education - Yahaya, Azizi; Ramli, Jamaluddin; Hashim, Shahrin; Ibrahim, Mohd. Ali; Zakaria, Zurihanmi (Science Publications, 2009)
Problem statement: With the advent of improved psychiatric medication, there has been a phenomenal increase of students with psychiatric disabilities studying at higher education in North America. Similarly in Malaysia and unaware to many, there has been a growing number of such a population. The aim of this research was to determine the demographic characteristics of students with psychiatric disabilities studying at higher education in Johore and their level of performance at four related variables (coping difficulties, symptomatology, self-esteem and academic achievement). The survey was conducted at Sultanah Aminah Hospital and Permai Hospital, Johore. (The pilot study was done in Sarawak General Hospital, Kuching.) Approach: Data from a sample of 30 respondents was collected using a questionnaire and analyzed using the Statistical Package for Social Sciences (SPSS) v.13. Results: Besides reporting descriptive statistics on demographic characteristics, their level of coping difficulties at school was found to be low, illness symptoms low, self-esteem high and academic achievement at a good GPA mean of 3.03 (out of a 4 point system). The findings imply coping difficulties experienced, that they do not pose a danger, the role change to being a â€œstudentâ€? assisted recovery and the findings also imply the capability to pursue educational goals. Conclusion: Recommendations were thus made to professionals and co-workers, as well as policy makers (the latter regarding the proposed Persons with Disabilities Act 2002).